The Use of Aerial Photograph and Remote Sensing System in the Study of Mass Movement Hazards the Kulekhani Watershed Region in Central Nepal - Manandhar, Indra Narayan (Himalayan Review, 2011)
Not available. Key words: Aerial Photograph; Remote Sensing System; Mass Movement Hazards; Kulekhani Watershed The Himalayan Review Nepal Geographical Society Vol. XVII-XIX 1986-1988 Page: 40-62 Uploaded date: 2 June, 2011